The serodiagnosis of infection with Salmonella typhi. Issue 11 (1st November 2000) - Chart, H; Cheesbrough, J S; Waghorn, D J
Abstract : Background/Aims —The serodiagnosis of infection with Salmonella typhi, using the Widal agglutination assay, relies on patients' antibodies to the O=9, 12 lipopolysaccharide (LPS) antigens, H=d flagellar antigens, and the Vi capsular antigens. A Vi agglutination titre of > 1/40 has traditionally been regarded as indicative of recent infection with S typhi. In this study, 91 sera were used to assess the reliability of the Widal agglutination assay based on antibodies to the Vi antigens. Methods —The Widal agglutination assay was carried out using protocols established by the Central Public Health Laboratory, Colindale. Antibodies to the Vi capsular antigen were detected using a standard preparation of S typhi, ViI Bhatnagar variant strain ( S typhi, ViI). Sera used in the study comprised 73 from patients who were culture positive for S typhi, 10 from patients who were culture positive for other species of Salmonella not expressing a Vi antigen (namely, S javiana, S enteritidis, S typhimurium, S stanley, S saint paul, S bareilly, or S mbandaka ), and eight from healthy blood donors. Results —Agglutination titres of ≥ 1/40 were detected to S typhi ViI in 69 of 73 sera from patients with typhoid, although 27 of these also agglutinated an unrelated control antigen. The Widal assay also detected significant amounts of agglutinating antibodies to S. typhi ViI in all eight control sera and seven sera from patients infected with S bareilly, S enteritidis, S javiana, S mbandaka, S saint paul, and S stanley. Conclusions —Agglutinating antibodies to the Vi antigen can be detected by the Widal assay, but even with the appropriate control antigens the results were unreliable. The serodiagnosis of infections with S typhi should be based on the detection of antibodies to both the O=9, 12 LPS antigen and the H=d flagellar antigen by immunoblotting, and should not use the Vi antigen-based Widal assay. Conclusions should be made in the light of patients' clinical details and any knowledge of previous immunisation for typhoid.